Convergence of Artificial Intelligence, Emotional Intelligence, Neural Network and Evolutionary Computing - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
This paper presents a new perspective of Artificial Intelligence (AI). Although, number of attempts has been made to make an artifact intelligent, including evolution theory, neural network etc and a number of problems have been solved using these concepts but each of this theory covers only some aspect of human intelligence. Still there is a large gap between artificial intelligence agent and human being. Instrumental convergence is the hypothetical tendency for most sufficiently intelligent agents to pursue certain instrumental goals such as self-preservation and resource acquisition. Instrumental convergence suggests that an intelligent agent with apparently harmless goals can act in surprisingly harmful ways. For example, a computer with the sole goal of solving the Riemann hypothesis could attempt to turn the entire Earth into computronium in an effort to increase its computing power so that it can succeed in its calculations.